Consumo y uso del aceite de copaiba (Copaifera officinalis) con fines comerciales en la ciudad de Iquitos-2018 - Barrera Meza, Elmer Alberto (2022)
The study was developed in Iquitos; District of Nativity passage "Paquito", place where medicinal plants, resins, and other species of healing properties are expended. The objective was to determine the current situation of the consumption and use of the oil of Copaiba with commercial ends in the city of Iquitos. The sample was represented by 30 people, the results of the survey were; 66,7% of those interviewed is of the feminine gender; 43,3% is convivences; 56,7% resides in the district of Iquitos; with respect to the stratum economic partner the 40 / they are of half condition; 63,3% has primary instruction; 26,7% knows the copaiba and the cat fingernail and 20% he/she knows the achiote like medicinal plant; 33,3% says that the copaiba oil cures the gastritis and you ulcerate them, 40% says that the demand of the oil is daily and 23,3% says that it is weekly and monthly; 70% says that the consumption is less than a liter; the sale container with more demand is the dropper with 63,3% and the flask of 125 ml has a demand of 33,3%; 46,7% says that the price is exactly and it satisfies the client; 20% of the clients accepts this price; with respect to the continuity in the market if the product was industrialized 56% I say that it would not continue and with respect to the client's continuity if the product would be industrialized 56,7% he/she responded that not. When applying the non-parametric test of square Ji (X2), with a significances level of = 0.05 for the recruiting of the hypotheses, it was found that a significant statistical relationship exists among the knowledge of the medicinal plants with the sex, it demands of the copaiba oil and the instruction degree and the container type used with the sale price. Being concluded that he/she wastes away oil of Copaiba in the market of Iquitos", which has perspectives of more commercial development.